Comparative Evaluation of Hyoid Bone Position and Tongue Area with Twin Block and Forsus: A Randomized Clinical Trial - Rajput, Raksha; Daokar, Suchita (Orthodontic Journal of Nepal, 2020)
Introduction: Class II div 1 malocclusion is most commonly presented with retruded mandible. This backward placement of mandible pushes the tongue posteriorly and inturn impairs the position of hyoid bone and total tongue area. Correction of retruded mandible with functional appliances is also considered to have positive effect on hyoid bone position and tongue area. Aim and Objectives: The objective of this study was to evaluate and compare the effects of Twin Block and Forsus on the hyoid bone position and tongue area in the treatment of Class II division 1 malocclusion. Materials & Method: A 2-arm parallel, randomized controlled trial was designed consisting of 24 Class II division 1 malocclusion patients indicated for treatment with functional appliances. 24 patients were randomized and equally divided among Twin Block (Group A) and Forsus (Group B) group. Pre- and post functional lateral cephalograms of both groups were traced and statistically analysed using paired t-test and T test of Equality of Means. ‘p’ value of less than 0.05 was considered as statistically significant. Result: A significantly upward and forward movement of hyoid bone was found with both the appliances. Tongue area also improved with Twin Block and Forsus group. On intergroup comparison insignificant results were observed between both the appliances indicating similar effect on tongue area and hyoid bone position. Conclusion: Twin Block has more skeletal effect than Forsus, still both Twin Block and Forsus are effective in improving tongue area and forward and upward displacement of hyoid bone position while correcting Class II malocclusion.